Intellectual property in chemistry : a guide to applying for and obtaining a patent for graduate students and postdoctoral scholars /: a guide to applying for and obtaining a patent for graduate students and postdoctoral scholars. (2018) - Duran, Nelson; Fonseca, Leandro Carneiro; Seabra, Amedea B
No abstract available